2012
DOI: 10.21608/jappmu.2012.83311
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of New Nutritional Resources in Ruminant Feeding (3) Effect of Using Dried Distillers Grains With Solubles (Ddgs)as Protein Source in Rations for Lactating Friesian Cows

Abstract: This trial aimed to study the effect of using dried distillers grains with soluble (DDGS) at different levels as partial substitute for protein sources in rations of lactating Friesian cattle. Twenty five Friesian cows were chosen and used in feeding trial (which lasted 210 days) during year of 2011. Animals were divided into five similar groups, which received concentrate feed mixture containing DDGS at rate of 0, 11, 16, 21 and 27% to cover 0, 20, 30, 40 and 50% of the dietary protein content, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(30 reference statements)
1
0
0
Order By: Relevance
“…It could be noticed that using cotton seed cake, soybean meal or DDGS as a source of protein in ration of lactating Friesian cows tended to higher milk yield and its composition. These results were in agreement with those reported by Etman et al (2012) who found that actual and 4% FCM yields increased with increasing dried distiller grains with soluble as a source of protein in rations of lactating Friesian cows. On the other hand, Anderson et al (2006), Janicek et al (2008), Kelzer et al (2009) and Zhang et al (2010) showed higher milk yield with increasing DDGS levels in rations of lactating cows.…”
Section: Resultssupporting
confidence: 93%
“…It could be noticed that using cotton seed cake, soybean meal or DDGS as a source of protein in ration of lactating Friesian cows tended to higher milk yield and its composition. These results were in agreement with those reported by Etman et al (2012) who found that actual and 4% FCM yields increased with increasing dried distiller grains with soluble as a source of protein in rations of lactating Friesian cows. On the other hand, Anderson et al (2006), Janicek et al (2008), Kelzer et al (2009) and Zhang et al (2010) showed higher milk yield with increasing DDGS levels in rations of lactating cows.…”
Section: Resultssupporting
confidence: 93%